PELATIHAN KOMUNIKASI DAKWAH DIGITAL BAGI KADER ULAMA MUI JAKARTA UTARA - Endang Suryani, Rahayu; Herminda, Herminda; Rahmat Kabul, Eka; Yulius, Yosandi; Masruhin, Masruhin; Muksin, Abdullah; Edi Utami, Nastiti; Kuswanti, Kuswanti (Universitas Mataram, 2024)
ABSTRACT Ulama have the duty and responsibility to continue carrying out prophetic (prophetic) duties and continue the mission of Rasulullah SAW, namely bringing Islamic teachings that are rahmatan lil 'alamin through da'wah activities, both offline and online. Da'wah communication is the process of conveying information from a person or group to another person or group of people sourced from the Al-Quran and Hadith by using symbols, both verbal and non-verbal. The aim of this da'wah communication training is to change the attitudes, opinions and behavior of preachers to be better in accordance with Islamic teachings through digital social media. Da'wah activities via social media are very widespread and attract the attention of all parties. The training method is carried out through providing communication materials, da'wah materials, use of digital social media and group discussions. The training participants are millennial Dai within the North Jakarta MUI. The results of the training show that there is an understanding of communicating in digital social media and that millennial Dais are more confident in preaching. It was concluded that digital da'wah communication training is really needed so that millennial Dai can spread Islamic teachings more effectively in the era of digitalization.